PENGARUH EASE OF USE, USEFULNESS, DAN USER INTERFACE APLIKASI BSI MOBILE TERHADAP MINAT GENERASI MILENIAL DAN GENERASI Z UNTUK MELAKUKAN PEMBELIAN EMAS PADA PLATFORM BSI MOBILE - Attarsyah, Azriel Auqi; Supriani, Indri (Islamic Economics and finance in Focus, 2024)
In the past two decades technology has been developing rapidly, whereas a lot of sectors in the economy are digitized. One of the examples are BSI mobile platform that has been rapidly growing because of the majority peoples religion in indonesia is in fact Islam. The purpose of this research is to analyze the effect of BSI mobile platform Ease of use, Usefulness, User interface towards Millennials Generation and Z Generation interest to buy gold by using BSI mobile features called e-emas. This research is using questionnaires to gather data from the respondents which then are going to be processed using the SEM-PLS method. The Questionnaires will be made with Google Forms that are going to be shared in several social media platform. The results of this study shows that Ease of Use and Usefulness of BSI mobile platform does not have significant effect towards Millennials and Z generation interest to buy gold via BSI mobile platform. In contrast, User interface does have a significant effect towards Millennials and Z generation interest in buying gold through BSI mobile platform. Researcher hoped that this study could give insight and also an overview for the consumer about BSI mobile mechanism for consideration, then could also be a reference for the next researcher that studies about BSI mobile platform specifically on e-emas features.